2019
DOI: 10.1111/myc.12892
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal susceptibility of yeast bloodstream isolates collected during a 10‐year period in Austria

Abstract: Summary Background Candida‐associated infections put a significant burden on western healthcare systems. Development of (multi‐)resistant fungi can become untreatable and threaten especially vulnerable target groups, such as the immunocompromised. Objectives We assessed antifungal susceptibility and explored possible influence factors of clinical Candida isolates collected from Austrian hospitals between 2007 and 2016. Methods Thousand three hundred and sixty clinical Candida spp. isolated from blood cultures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
4
11
1
Order By: Relevance
“…The susceptibility of Asian strains to azoles is lower than that of Europe, America, and Oceania, and FNS CCs have not been seen outside Asia. This is consistent with many previous studies (Corzo-Leon et al, 2014;Huang et al, 2014;Fernández-Ruiz et al, 2015;Tan et al, 2016;Wang H. et al, 2016;Fan et al, 2017;Teo et al, 2017;Wu P. F. et al, 2017;Morris et al, 2018;Scordino et al, 2018;Beyer et al, 2019;Chen et al, 2019). Three FNS CCs from three Asian countries With pulmonary candidiasis: A total of 4 cases.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The susceptibility of Asian strains to azoles is lower than that of Europe, America, and Oceania, and FNS CCs have not been seen outside Asia. This is consistent with many previous studies (Corzo-Leon et al, 2014;Huang et al, 2014;Fernández-Ruiz et al, 2015;Tan et al, 2016;Wang H. et al, 2016;Fan et al, 2017;Teo et al, 2017;Wu P. F. et al, 2017;Morris et al, 2018;Scordino et al, 2018;Beyer et al, 2019;Chen et al, 2019). Three FNS CCs from three Asian countries With pulmonary candidiasis: A total of 4 cases.…”
Section: Discussionsupporting
confidence: 92%
“…Studies in Asia have shown that the non-susceptible rate of C. tropicalis to fluconazole is around 20% (mostly cross-resistant with other azoles) and increases rapidly (Wang H. et al, 2016;Fan et al, 2017;Chen et al, 2019). However, fluconazole-nonsusceptible (FNS) C. tropicalis is relatively rare in Europe and America (Corzo-Leon et al, 2014;Scordino et al, 2018;Beyer et al, 2019). Some studies support the link between FNS C. tropicalis infections and prior antifungal exposure (Choi et al, 2016;Chen et al, 2019), whereas others suggest that FNS C. tropicalis may come from the environment (Lo et al, 2017;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Alarmingly, in the candidemia studies conducted in South Africa (Govender et al, 2016) and Turkey (Hilmioglu-Polat et al, 2018) almost half of FLZ-R isolates were crossresistant to VRZ. Similar to South Africa (Govender et al, 2016), Turkey (Hilmioglu-Polat et al, 2018), Qatar (Taj-Aldeen et al, 2018), Asia-Pacific countries (Tan et al, 2016), Spain and Italy (Bassetti et al, 2013;Tortorano et al, 2013), and Austria (Beyer et al, 2019) that showed low levels of echinocandin resistance (except for one MCF-R isolate), our isolates were susceptible to this antifungal class. We assume that such a low level of antifungal resistance in our study might be explained by the lack of previous and prolonged antifungal exposure (Ii et al, 2013;Perlin, 2015) and the fact that prophylactic antifungal therapy is not well-exercised in many Iranian hospitals.…”
Section: Discussionsupporting
confidence: 70%
“…The overall low rate of antifungal resistance is similar to what is observed in several European countries (Austria, Italy, and Spain) and Asia Pacific countries (Bassetti et al, 2013;Tortorano et al, 2013;Tan et al, 2016;Beyer et al, 2019), but quite different from studies conducted in the USA, South Africa, and India with surprisingly high rates of azole resistance (Raghuram et al, 2012;Govender et al, 2016;Singh et al, 2019). Alarmingly, in the candidemia studies conducted in South Africa (Govender et al, 2016) and Turkey (Hilmioglu-Polat et al, 2018) almost half of FLZ-R isolates were crossresistant to VRZ.…”
Section: Discussionsupporting
confidence: 59%
“…Because all of strains published by AURES are collected at our department we retested all strains in order to confirm the published resistance data [12]. The MICs of fluconazole, voriconazole, posaconazole, itraconazole, isavuconazole, anidulafungin, caspofungin, and micafungin of all isolates were determined while using the microdilution reference method as described by EUCAST.…”
Section: Introductionmentioning
confidence: 99%